2021
DOI: 10.1002/aqc.3515
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian modelling suggests that the sterlet (Acipenser ruthenus, Linnaeus 1758) population is ageing in the middle Danube River

Abstract: In the past, sturgeons played an important role in commercial and recreational fisheries in the Danube River and its tributaries. Human impacts in the Danube River Basin coupled with exploitation of sturgeon stocks led to all species being either locally extinct, critically endangered or of unknown status. Sterlet (Acipenser ruthenus, Linnaeus 1758) is the last known sturgeon species occurring in the upper and middle Danube; however, the population of this species is considered unbalanced and decreasing since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, despite being of a certain economic value in the Middle and Lower Danube catchments (Guti 2008;Vassilev and Pehlivanov 2003), the current status of the population remains almost completely unknown, although the consensus among most authors is that stocks are declining (e.g. Bacalbasa-Dobrovici 1991;Paraschiv et al 2006) and aging (Kubala et al 2021). In the present study, approximately half of the samples collected from the Danube yielded a positive signal for the sterlet, and notably, we identified 3 areas with higher densities of this species, as indicated by a high frequency of detection and a high number of reads (namely, the Danube Delta, Iron Gate to Belgrade, and Budapest to Gabčíkovo sections of the river).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite being of a certain economic value in the Middle and Lower Danube catchments (Guti 2008;Vassilev and Pehlivanov 2003), the current status of the population remains almost completely unknown, although the consensus among most authors is that stocks are declining (e.g. Bacalbasa-Dobrovici 1991;Paraschiv et al 2006) and aging (Kubala et al 2021). In the present study, approximately half of the samples collected from the Danube yielded a positive signal for the sterlet, and notably, we identified 3 areas with higher densities of this species, as indicated by a high frequency of detection and a high number of reads (namely, the Danube Delta, Iron Gate to Belgrade, and Budapest to Gabčíkovo sections of the river).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of multiple acipenseriform species highlighted the need to extend monitoring and management activities beyond pre‐established jurisdictional boundaries (Tripp et al, 2019). Kubala et al (2021) also called for the collaborative planning of monitoring efforts, given the propensity of sturgeon species to cross jurisdictional boundaries. This could also be important for early life stages, as Lechner, Keckeis & Humphries (2016) suggested that understanding drift dynamics of eggs, free embryos, and larvae is critical for managing a variety of river fishes, including both common and rare species.…”
Section: Discussionmentioning
confidence: 99%
“…country borders or state lines) that have different management priorities, monitoring plans, and species protections. This is often the case for acipenseriform species such as sturgeons, and can lead to varying designations of species status, depending on location (Kubala et al, 2021). Recent work has highlighted the importance of inter‐jurisdictional management and collaboration to better account for the large‐scale movement of river fishes.…”
Section: Introductionmentioning
confidence: 99%